The Use Of Learning Media on Students' Learning Outcomes - Rusdianto Muhamad; Melizubaida Mahmud; Agil Bahsoan; Sudirman Sudirman (Journal of Economic and Business Education, 2023)
The purpose of this study was to determine the effect of learning media on student learning outcomes in integrated social studies subjects at State Junior High Schools 1 Bulango Utara. This study uses a quantitative approach, with survey research methods. The data used are primary data obtained from distributing questionnaires to class VIII students of State Junior High Schools 1 Bulango Utara. The number of sampling in this study amounted to 32 respondents. The data analysis technique used simple linear regression. The results of the study indicate that there is an influence of learning media on student learning outcomes for integrated social studies subjects for class VIII State Junior High Schools 1 Bulango Utara. The magnitude of the influence of Learning Media on Student Learning Outcomes is 22.7% while the remaining 77.3% is influenced by variables not examined.